Polycarbonate material as well as preparation method and application thereof

By using composite flame retardant with nitrogen oxygen radicals in polycarbonate materials, the problem of insufficient impact resistance and flame retardant performance of the material in low temperature environments is solved, and efficient low-temperature impact performance and ultra-thin flame retardant effect are achieved.

CN119798946APending Publication Date: 2025-04-11CHONGQING ORINKO TECH CO LTD CHINA

Patent Information

Application Number
CN202411972574.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

Polycarbonate materials have poor impact resistance and poor flame retardant performance in low temperature environments, which limits their application scenarios.

Method used

A composite flame retardant is used, which is made of an organic silicon flame retardant with nitrogen oxygen radicals on the structure. It combines with the nitrogen oxygen radical compound containing active groups through group reaction to form a material with high-efficiency flame retardant properties.

Benefits of technology

Under a low temperature environment of minus 40℃, the material exhibits good impact resistance and achieves ultra-thin flame retardant effect of 0.5 to 0.8mm, has excellent weather resistance and flame retardant performance, and is suitable for mid-to-high-end electronic and electrical appliance fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005219778430000061
    Figure BDA0005219778430000061
  • Figure BDA0005219778430000161
    Figure BDA0005219778430000161
  • Figure BDA0005219778430000162
    Figure BDA0005219778430000162
Patent Text Reader

Abstract

The invention discloses a polycarbonate material as well as a preparation method and application thereof, and belongs to the technical field of high polymer materials, and the polycarbonate material is prepared from the following raw materials in parts by weight: 40-80 parts of polycarbonate, 20-60 parts of silicon copolymerized polycarbonate, 0.1-0.5 part of a sulfonate flame retardant, 0.1-0.5 part of a compound flame retardant, 0.3-0.8 part of an anti-dripping agent, 0.1-0.4 part of an antioxidant and 0.2-0.8 part of a lubricant. The compound flame retardant is an organic silicon flame retardant with free radicals of nitrogen and oxygen in structure. The material still has better impact resistance in a low-temperature environment of minus 40 DEG C; the compound flame retardant not only has an efficient flame retardant effect, but also has excellent weather resistance; under the action of a sulfonate flame retardant and a compound flame retardant, the flame retardant can meet the flame retardant requirement of 0.5-0.8 mm ultrathin parts, and is especially suitable for the field of electronic and electrical appliances such as middle-and-high-end notebook computers, electronic book shells and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polymer materials, and in particular relates to a polycarbonate material and a preparation method and application thereof. Background Art

[0002] Polycarbonate has excellent comprehensive performance and good transparency. It is one of the most widely used and fastest-growing engineering plastics. At the same time, it has good dimensional stability, mechanical properties, thermoelectric properties, and creep resistance. Therefore, it is widely used in various fields of national production and life such as machinery, electronics, electrical appliances, and textiles. With the updating and iteration of products, the lightweighting of plastic products has become an important development direction. Plastic products are becoming thinner and thinner, and the flame retardant properties of materials are becoming more and more demanding. In addition, conventional polycarbonate has poor impact strength in a low temperature environment of minus 40°C, which also limits the application scenarios of polycarbonate materials.

[0003] Thin-wall flame-retardant polycarbonate materials are often compounded with silicone flame retardants for flame retardancy. For example, when cage-type polysilsesquioxane flame retardants are added, when the polymer material burns and decomposes, the silicone flame retardant will be oxidized and decomposed to form a silicate layer to isolate the air, thereby playing a flame retardant role. Using silicone flame retardants alone cannot achieve thin-wall flame retardancy. The patent application with publication number CN106349676A discloses a halogen-free flame-retardant PC and its preparation method. The specific raw material formula is as follows: polycarbonate 65-80%, polycarbonate powder 10-25%, flame retardant 2.5-6.5%, anti-dripping agent 0.2-0.5%, modified filler 2-5%, carbon black 0.5-1%, antioxidant 0.5-1%, lubricant 0.2-1%. The invention application uses a flame retardant system compounded with sulfonate and silicone, and the result can reach 0.25mm UL94V-0 level, but the invention is brittle in impact performance under low temperature environment.

[0004] The chain reaction generated by polymer materials during combustion will release a large number of active free radicals (such as OH·, O·, H·). The hydrogen halide produced by halogen flame retardants can capture the above active free radicals, and the generated halogen free radicals can continue to participate in the reaction, thus blocking the combustion reaction in a cycle. However, a large amount of smoke and toxic and corrosive gases will be released during the combustion of halogen flame retardants. Although halogen flame retardants have the advantages of high flame retardant efficiency and wide adaptability, their shortcomings in safety and environmental protection limit their application in polycarbonate materials. Summary of the invention

[0005] The object of the present invention is to provide a polycarbonate material and a preparation method and application thereof, so as to solve the problem that the polycarbonate material has poor flame retardancy.

[0006] The purpose of the present invention can be achieved by the following technical solutions:

[0007] To achieve the above objectives, the first aspect of the present invention provides a polycarbonate material, wherein the raw materials for preparation include, by weight, 40 to 80 parts of polycarbonate, 20 to 60 parts of silicon copolymer polycarbonate, 0.1 to 0.5 parts of sulfonate flame retardant, 0.1 to 0.5 parts of compound flame retardant, 0.3 to 0.8 parts of anti-dripping agent, 0.1 to 0.4 parts of antioxidant and 0.2 to 0.8 parts of lubricant, wherein the compound flame retardant is an organic silicon flame retardant having a nitroxide free radical in its structure, and the compound flame retardant is obtained by a group reaction between an organic silicon flame retardant containing an active group and a nitroxide free radical compound containing an active group.

[0008] Nitrogen oxide free radicals that are stable at room temperature can also quickly capture active free radicals such as C·, O2·, O·, OH· and H·, and have an active free radical quenching effect, thus showing flame retardant potential. Nitrogen oxide free radicals can be stable at room temperature and have the characteristics of effectively capturing active free radicals generated by light, heat, and oxidative degradation of polymers. Therefore, polycarbonate materials with compound flame retardants have excellent weather resistance.

[0009] Furthermore, the mass ratio of polycarbonate to silicon copolymer polycarbonate is less than 1.5.

[0010] Furthermore, the polycarbonate is bisphenol A polycarbonate, and the melt mass flow rate is 3 to 20 g / 10 min;

[0011] And / or, the silicon copolymer polycarbonate melt has a mass flow rate of 3 to 10 g / 10 min;

[0012] Furthermore, the sulfonate flame retardant includes at least one of potassium benzenesulfonylbenzenesulfonate, potassium perfluorobutylsulfonate and sodium 2,4,5-trichlorobenzenesulfonate.

[0013] Furthermore, the organosilicon flame retardant is a cage-type polysilsesquioxane (POSS), and the general formula of the cage-type polysilsesquioxane (POSS) is (RS iO3 / 2)n, wherein n is an even number ≥6, and R is an organic group connected to the Si atom.

[0014] Furthermore, the organic group in the structure of the organosilicon flame retardant is an active group, and the number of the active group is at least one.

[0015] Furthermore, the active group in the structure of the organosilicon flame retardant is selected from one of epoxy, carboxyl, hydroxyl, amino, isocyanate, vinyl, allyl and thiocyanate.

[0016] Further, the organosilicon flame retardant is any one of octaepoxy cage-type polysilsesquioxane (epoxy-POSS), octavinyl cage-type polysilsesquioxane (vinyl-POSS), octaglycidyl cage-type polysilsesquioxane (glycidyl-POSS), octacarboxyl cage-type polysilsesquioxane, acrylate cage-type polysilsesquioxane, allyl isobutyl cage-type polysilsesquioxane, trinorbornene isobutyl cage-type polysilsesquioxane, epoxy cyclohexyl cage-type polysilsesquioxane, trisilanol phenyl cage-type polysilsesquioxane, and octaammonium cage-type polysilsesquioxane.

[0017] The general formula of nitroxide free radical compounds is R>(NO·)x, where R is an active group and the value of x is a positive integer.

[0018] Furthermore, the structure of the nitroxide free radical compound contains at least one nitroxide free radical.

[0019] Furthermore, the nitroxide free radical compound has at least one active group in its structure.

[0020] Furthermore, the active group in the structure of the nitroxide free radical compound is selected from one of epoxy, carboxyl, hydroxyl, amino, isocyanate, vinyl, allyl and thiocyanate.

[0021] Further, the nitroxide free radical compound is 2,2,6,6-tetramethylpiperidine-1-oxyl-4-amino-4-carboxylic acid, 4-(2-bromoacetamide)-2,2,6,6-tetramethylpiperidine-1-oxyl free radical, 4-epoxypropyloxy-2,2,6,6-tetramethylpiperidine-1-oxyl free radical, 4-amino-2,2,6,6-tetramethylpiperidine-1-oxyl free radical, 4-hydroxy-2,2,6,6-tetramethylpiperidine nitroxide free radical, 4-carboxyl-2,2,6,6-tetramethylpiperidine-1-oxyl free radical, 4 -One of the following: isocyanate-2,2,6,6-tetramethylpiperidine-1-oxyl free radical, 4-isothiocyanate-2,2,6,6-tetramethylpiperidine-1-oxyl free radical, 4-methacryloyloxy-2,2,6,6-tetramethylpiperidine-1-oxyl free radical, 4-(4-chloroformyl-benzoate)-2,2,6,6-tetramethylpiperidine-1-oxyl free radical, 3-carbamoyl-2,2,5,5-tetramethyltetrahydropyrrole nitrogen oxide free radical, and 3-carboxy-2,2,5,5-tetramethylpyrrolidine-1-oxyl free radical.

[0022] Further, the preparation process of the compound flame retardant is as follows:

[0023] A catalyst is added to a solvent of an organosilicon flame retardant containing an active group and a nitroxide free radical compound containing an active group, the reaction temperature is 20 to 60° C., the reaction is stirred for 6 to 24 hours, and then the mixture is extracted and dried.

[0024] Further, the anti-drip agent is a polytetrafluoroethylene anti-drip agent coated with acrylonitrile-styrene copolymer;

[0025] and / or, the antioxidant comprises at least two of antioxidant 1076, antioxidant 1010, antioxidant 168, and antioxidant 627A;

[0026] And / or, the lubricant is at least one of pentaerythritol stearate, silicone powder and polyester wax.

[0027] Accordingly, the second aspect of the present invention provides a method for preparing a polycarbonate material, comprising the steps of:

[0028] (1) Mixing: Mixing the formulated amounts of polycarbonate, silicon copolymer polycarbonate, sulfonate flame retardant, compound flame retardant, anti-dripping agent, antioxidant and lubricant to obtain a mixed material;

[0029] (2) Extrusion granulation: adding the mixed material to a twin-screw extruder for granulation to obtain a high-toughness, thin-wall, halogen-free, flame-retardant polycarbonate material.

[0030] Further, the processing temperature of each zone of the twin-screw extruder is: the temperature of zone 1 is 225°C±5°C, the temperature of zone 2 is 255°C±5°C, the temperature of zone 3 is 255°C±5°C, the temperature of zone 4 is 255°C±5°C, the temperature of zone 5 is 265°C±5°C, the temperature of zone 6 is 265°C±5°C, the temperature of zone 7 is 275±5°C, the temperature of zone 8 is 275±5°C, the temperature of zone 9 is 265±5°C, and the temperature of zone 10 is 265±5°C. The head temperature is 285°C±5°C, the screw speed is 300rpm~400rpm, and the vacuum degree is -0.5MPa~-0.9MPa.

[0031] Correspondingly, the third aspect of the present invention provides an application of the above-mentioned high-toughness thin-walled halogen-free flame-retardant polycarbonate material in a manufactured article.

[0032] As a technical solution of the present invention, the thickness of the high-toughness thin-wall halogen-free flame-retardant polycarbonate material product is 0.5-0.8 mm.

[0033] Beneficial effects of the present invention:

[0034] (1) The material prepared by the present invention still has good impact resistance in a low temperature environment of -40°C.

[0035] (2) Under the action of sulfonate flame retardant and compound flame retardant, the material prepared by the present invention can achieve ultra-thin flame retardancy of 0.5 to 0.8 mm;

[0036] The high-toughness thin-walled halogen-free flame-retardant polycarbonate material of the present invention has high low-temperature impact performance, good weather resistance, and excellent flame retardant properties, and can meet the flame retardant requirements of 0.5-0.8mm ultra-thin parts, and is particularly suitable for electronic and electrical fields such as mid-to-high-end laptop computers and e-book shells.

[0037] (3) The nitroxide free radicals on the composite flame retardant of the present invention can play the same weathering principle as the hindered amine light stabilizer. Without adding any additional ultraviolet absorber or light stabilizer, it not only has a highly efficient flame retardant effect, but also has excellent weathering resistance.

[0038] The compound flame retardant of the present invention not only exerts the flame retardant performance of the organosilicon flame retardant, but also exerts the characteristic that the nitroxide free radical can capture active free radicals, so that the compound flame retardant has high-efficiency flame retardant performance.

[0039] The present invention prepares an organosilicon flame retardant with a nitroxide free radical structure, namely a compound flame retardant, which not only exerts the flame retardant properties of organosilicon, but also exerts the characteristics of nitroxide free radicals that can capture active free radicals, so that it has a highly efficient flame retardant effect. In the case where no ultraviolet absorber or light stabilizer is added to the polycarbonate material, the nitroxide free radicals on the compound flame retardant of the present invention can exert the same weather resistance principle as the hindered amine light stabilizer, and on the basis of improving the ultra-thin flame retardant properties, simultaneously give the material excellent weather resistance. A polycarbonate material with good low-temperature impact performance, good thin-wall flame retardant effect and excellent weather resistance has been developed. DETAILED DESCRIPTION

[0040] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0041] The test methods and standards used in the following examples and comparative examples are as follows:

[0042] Tensile strength test: carried out in accordance with ASTM D638 standard, with a tensile speed of 50 mm / min.

[0043] Izod notched impact test: tensile properties were tested according to ASTM D256; low temperature notched impact test conditions: the test specimens were placed in a -40°C refrigerator for 4 hours and then taken out to test the Izod notched impact strength.

[0044] Flame retardant performance test: The flame retardant performance test was carried out in accordance with UL-94 standard, and the test specimens were 0.5mm and 0.8mm standard flame retardant specimens.

[0045] Xenon lamp aging test: According to GB / T16422.2-2022, the tensile specimens were subjected to aging test with an aging time of 1000 h, and the tensile strength retention rate and Izod notched impact retention rate after aging were calculated.

[0046] The specific information of the raw materials used in the following examples and comparative examples is as follows:

[0047]

[0048] Example 1

[0049] Octaglycidyl cage-type polysilsesquioxane (glycidyl-POSS) is dissolved in tetrahydrofuran in an equivalent ratio of 8:1 between the epoxy group and the hydroxyl group of 4-hydroxy-2,2,6,6-tetramethylpiperidinyl nitroxide free radical (4-OH-TEMPO), phosphoric acid is used as a catalyst, and the reaction is stirred at 40°C for 6 hours. After drying, a POSS grafted nitroxide free radical compound is obtained, which is a composite flame retardant.

[0050] 58.5 parts of polycarbonate, 40 parts of silicon copolymer polycarbonate, 0.3 parts of potassium benzenesulfonylbenzenesulfonate flame retardant, 0.1 parts of compound flame retardant, 0.4 parts of anti-dripping agent, 1680.1 parts of antioxidant, 10760.1 parts of antioxidant, and 0.4 parts of pentaerythritol stearate. (1) Mixing: Add the above-mentioned formula components into a high-speed mixer and stir for 5 minutes to obtain a mixed material; (2) Extrusion granulation: Add the mixed material into a twin-screw extruder for granulation. The processing temperature of each section of the twin-screw extruder is as follows: the temperature of the first section is 225°C ± 5°C, the temperature of the second section is 255°C ± 5°C, the temperature of the third section is 255°C ± 5°C, the temperature of the fourth section is 255°C ± 5°C, the temperature of the fifth section is 265°C ± 5°C, the temperature of the sixth section is 265°C ± 5°C, the temperature of the seventh section is 275±5°C, the temperature of the eighth section is 275±5°C, the temperature of the ninth section is 265±5°C, and the temperature of the tenth section is 265±5°C. The head temperature is 285°C ± 5°C, the screw speed is 300rpm~400rpm, and the vacuum degree is -0.5MPa~-0.9MPa.

[0051] Example 2

[0052] Octaglycidyl cage-type polysilsesquioxane (glycidyl-POSS) is dissolved in tetrahydrofuran in an equivalent ratio of 8:1 between the epoxy group and the hydroxyl group of 4-hydroxy-2,2,6,6-tetramethylpiperidinyl nitroxide free radical (4-OH-TEMPO), phosphoric acid is used as a catalyst, and the reaction is stirred at 40°C for 6 hours. After drying, a POSS grafted nitroxide free radical compound is obtained, which is a composite flame retardant.

[0053] 58.5 parts of polycarbonate, 40 parts of silicon copolymer polycarbonate, 0.3 parts of potassium benzenesulfonylbenzenesulfonate flame retardant, 0.2 parts of compound flame retardant, 0.4 parts of anti-dripping agent, 1680.1 parts of antioxidant, 10760.1 parts of antioxidant, and 0.4 parts of pentaerythritol stearate. (1) Mixing: Add the above-mentioned formula components into a high-speed mixer and stir for 5 minutes to obtain a mixed material; (2) Extrusion granulation: Add the mixed material into a twin-screw extruder for granulation. The processing temperature of each section of the twin-screw extruder is as follows: the temperature of the first section is 225°C ± 5°C, the temperature of the second section is 255°C ± 5°C, the temperature of the third section is 255°C ± 5°C, the temperature of the fourth section is 255°C ± 5°C, the temperature of the fifth section is 265°C ± 5°C, the temperature of the sixth section is 265°C ± 5°C, the temperature of the seventh section is 275±5°C, the temperature of the eighth section is 275±5°C, the temperature of the ninth section is 265±5°C, and the temperature of the tenth section is 265±5°C. The head temperature is 285°C ± 5°C, the screw speed is 300rpm~400rpm, and the vacuum degree is -0.5MPa~-0.9MPa.

[0054] Example 3

[0055] Octaglycidyl cage-type polysilsesquioxane (glycidyl-POSS) is dissolved in tetrahydrofuran in an equivalent ratio of 8:1 between the epoxy group and the hydroxyl group of 4-hydroxy-2,2,6,6-tetramethylpiperidinyl nitroxide free radical (4-OH-TEMPO), phosphoric acid is used as a catalyst, and the reaction is stirred at 40°C for 6 hours. After drying, a POSS grafted nitroxide free radical compound is obtained, which is a composite flame retardant.

[0056] 58.5 parts of polycarbonate, 40 parts of silicon copolymer polycarbonate, 0.3 parts of potassium benzenesulfonylbenzenesulfonate flame retardant, 0.3 parts of compound flame retardant, 0.4 parts of anti-dripping agent, 1680.1 parts of antioxidant, 10760.1 parts of antioxidant, and 0.4 parts of pentaerythritol stearate. (1) Mixing: Add the above-mentioned formula components into a high-speed mixer and stir for 5 minutes to obtain a mixed material; (2) Extrusion granulation: Add the mixed material into a twin-screw extruder for granulation. The processing temperature of each section of the twin-screw extruder is as follows: the temperature of the first section is 225°C ± 5°C, the temperature of the second section is 255°C ± 5°C, the temperature of the third section is 255°C ± 5°C, the temperature of the fourth section is 255°C ± 5°C, the temperature of the fifth section is 265°C ± 5°C, the temperature of the sixth section is 265°C ± 5°C, the temperature of the seventh section is 275±5°C, the temperature of the eighth section is 275±5°C, the temperature of the ninth section is 265±5°C, and the temperature of the tenth section is 265±5°C. The head temperature is 285°C ± 5°C, the screw speed is 300rpm~400rpm, and the vacuum degree is -0.5MPa~-0.9MPa.

[0057] Example 4

[0058] Trisilanol phenyl cage polysilsesquioxane is dissolved in tetrahydrofuran in an equivalent ratio of 3:1 between the hydroxyl group and the isocyanate group of 4-isocyanate-2,2,6,6-tetramethylpiperidin-1-oxyl free radical, dibutyltin dilaurate is used as a catalyst, and the reaction is stirred at 20°C for 24 hours. After drying, a POSS grafted nitroxide free radical compound is obtained, which is a composite flame retardant.

[0059] 58.5 parts of polycarbonate, 40 parts of silicon copolymer polycarbonate, 0.1 parts of potassium perfluorobutyl sulfonate flame retardant, 0.1 parts of compound flame retardant, 0.4 parts of anti-dripping agent, 1680.2 parts of antioxidant, 10760.2 parts of antioxidant, and 0.4 parts of pentaerythritol stearate. (1) Mixing: Add the above-mentioned formula components into a high-speed mixer and stir for 5 minutes to obtain a mixed material; (2) Extrusion granulation: Add the mixed material into a twin-screw extruder for granulation. The processing temperature of each section of the twin-screw extruder is as follows: the temperature of the first section is 225°C ± 5°C, the temperature of the second section is 255°C ± 5°C, the temperature of the third section is 255°C ± 5°C, the temperature of the fourth section is 255°C ± 5°C, the temperature of the fifth section is 265°C ± 5°C, the temperature of the sixth section is 265°C ± 5°C, the temperature of the seventh section is 275±5°C, the temperature of the eighth section is 275±5°C, the temperature of the ninth section is 265±5°C, and the temperature of the tenth section is 265±5°C. The head temperature is 285°C ± 5°C, the screw speed is 300rpm~400rpm, and the vacuum degree is -0.5MPa~-0.9MPa.

[0060] Example 5

[0061] Trisilanol phenyl cage polysilsesquioxane is dissolved in tetrahydrofuran in an equivalent ratio of 3:1 between the hydroxyl group and the isocyanate group of 4-isocyanate-2,2,6,6-tetramethylpiperidin-1-oxyl free radical, dibutyltin dilaurate is used as a catalyst, and the reaction is stirred at 20°C for 24 hours. After drying, a POSS grafted nitroxide free radical compound is obtained, which is a composite flame retardant.

[0062] 58.5 parts of polycarbonate, 40 parts of silicon copolymer polycarbonate, 0.1 parts of potassium perfluorobutyl sulfonate flame retardant, 0.2 parts of compound flame retardant, 0.4 parts of anti-dripping agent, 1680.2 parts of antioxidant, 10760.2 parts of antioxidant, and 0.4 parts of pentaerythritol stearate. (1) Mixing: Add the above-mentioned formula components into a high-speed mixer and stir for 5 minutes to obtain a mixed material; (2) Extrusion granulation: Add the mixed material into a twin-screw extruder for granulation. The processing temperature of each section of the twin-screw extruder is as follows: the temperature of the first section is 225°C ± 5°C, the temperature of the second section is 255°C ± 5°C, the temperature of the third section is 255°C ± 5°C, the temperature of the fourth section is 255°C ± 5°C, the temperature of the fifth section is 265°C ± 5°C, the temperature of the sixth section is 265°C ± 5°C, the temperature of the seventh section is 275±5°C, the temperature of the eighth section is 275±5°C, the temperature of the ninth section is 265±5°C, and the temperature of the tenth section is 265±5°C. The head temperature is 285°C ± 5°C, the screw speed is 300rpm~400rpm, and the vacuum degree is -0.5MPa~-0.9MPa.

[0063] Example 6

[0064] Trisilanol phenyl cage polysilsesquioxane is dissolved in tetrahydrofuran in an equivalent ratio of 3:1 between the hydroxyl group and the isocyanate group of 4-isocyanate-2,2,6,6-tetramethylpiperidin-1-oxyl free radical, dibutyltin dilaurate is used as a catalyst, and the reaction is stirred at 20°C for 24 hours. After drying, a POSS grafted nitroxide free radical compound is obtained, which is a composite flame retardant.

[0065] 58.5 parts of polycarbonate, 40 parts of silicon copolymer polycarbonate, 0.1 parts of potassium perfluorobutyl sulfonate flame retardant, 0.3 parts of compound flame retardant, 0.4 parts of anti-dripping agent, 1680.2 parts of antioxidant, 10760.2 parts of antioxidant, and 0.4 parts of pentaerythritol stearate. (1) Mixing: Add the above-mentioned formula components into a high-speed mixer and stir for 5 minutes to obtain a mixed material; (2) Extrusion granulation: Add the mixed material into a twin-screw extruder for granulation. The processing temperature of each section of the twin-screw extruder is as follows: the temperature of the first section is 225°C ± 5°C, the temperature of the second section is 255°C ± 5°C, the temperature of the third section is 255°C ± 5°C, the temperature of the fourth section is 255°C ± 5°C, the temperature of the fifth section is 265°C ± 5°C, the temperature of the sixth section is 265°C ± 5°C, the temperature of the seventh section is 275±5°C, the temperature of the eighth section is 275±5°C, the temperature of the ninth section is 265±5°C, and the temperature of the tenth section is 265±5°C. The head temperature is 285°C ± 5°C, the screw speed is 300rpm~400rpm, and the vacuum degree is -0.5MPa~-0.9MPa.

[0066] Example 7

[0067] Octacarboxyl cage-type polysilsesquioxane is dissolved in tetrahydrofuran in an equivalent ratio of 8:1 between carboxyl group and isocyanate group of 4-isocyanate-2,2,6,6-tetramethylpiperidin-1-oxyl free radical, with dimethylethanolamine as catalyst, and reacted at 60°C with stirring for 12h. After drying, a POSS grafted nitroxide free radical compound is obtained, which is a composite flame retardant.

[0068] 58.5 parts of polycarbonate, 40 parts of silicon copolymer polycarbonate, 0.2 parts of potassium benzenesulfonylbenzenesulfonate flame retardant, 0.1 parts of potassium perfluorobutyl sulfonate flame retardant, 0.2 parts of compound flame retardant, 0.4 parts of anti-dripping agent, 1680.2 parts of antioxidant, 10760.2 parts of antioxidant, and 0.4 parts of pentaerythritol stearate. (1) Mixing: Add the above-mentioned formula components into a high-speed mixer and stir for 5 minutes to obtain a mixed material; (2) Extrusion granulation: Add the mixed material into a twin-screw extruder for granulation. The processing temperature of each section of the twin-screw extruder is as follows: the temperature of the first section is 225°C ± 5°C, the temperature of the second section is 255°C ± 5°C, the temperature of the third section is 255°C ± 5°C, the temperature of the fourth section is 255°C ± 5°C, the temperature of the fifth section is 265°C ± 5°C, the temperature of the sixth section is 265°C ± 5°C, the temperature of the seventh section is 275±5°C, the temperature of the eighth section is 275±5°C, the temperature of the ninth section is 265±5°C, and the temperature of the tenth section is 265±5°C. The head temperature is 285°C ± 5°C, the screw speed is 300rpm~400rpm, and the vacuum degree is -0.5MPa~-0.9MPa.

[0069] Comparative Example 1

[0070] 58.5 parts of polycarbonate, 40 parts of silicon copolymer polycarbonate, 0.3 parts of potassium benzenesulfonylbenzenesulfonate flame retardant, 0.3 parts of silicone flame retardant (octaglycidyl cage polysilsesquioxane), 0.4 parts of anti-dripping agent, 1680.1 parts of antioxidant, 10760.1 parts of antioxidant, and 0.4 parts of pentaerythritol stearate. (1) Mixing: Add the above-mentioned formula components into a high-speed mixer and stir for 5 minutes to obtain a mixed material; (2) Extrusion granulation: Add the mixed material into a twin-screw extruder for granulation. The processing temperature of each section of the twin-screw extruder is as follows: the temperature of the first section is 225°C ± 5°C, the temperature of the second section is 255°C ± 5°C, the temperature of the third section is 255°C ± 5°C, the temperature of the fourth section is 255°C ± 5°C, the temperature of the fifth section is 265°C ± 5°C, the temperature of the sixth section is 265°C ± 5°C, the temperature of the seventh section is 275±5°C, the temperature of the eighth section is 275±5°C, the temperature of the ninth section is 265±5°C, and the temperature of the tenth section is 265±5°C. The head temperature is 285°C ± 5°C, the screw speed is 300rpm~400rpm, and the vacuum degree is -0.5MPa~-0.9MPa.

[0071] Comparative Example 2

[0072] 58.5 parts of polycarbonate, 40 parts of silicon copolymer polycarbonate, 0.3 parts of potassium benzenesulfonylbenzenesulfonate flame retardant, 0.3 parts of 4-hydroxy-2,2,6,6-tetramethylpiperidinium nitroxide free radical, 0.4 parts of anti-dripping agent, 1680.1 parts of antioxidant, 10760.1 parts of antioxidant, and 0.4 parts of pentaerythritol stearate. (1) Mixing: Add the above-mentioned formula components into a high-speed mixer and stir for 5 minutes to obtain a mixed material; (2) Extrusion granulation: Add the mixed material into a twin-screw extruder for granulation. The processing temperature of each section of the twin-screw extruder is as follows: the temperature of the first section is 225°C ± 5°C, the temperature of the second section is 255°C ± 5°C, the temperature of the third section is 255°C ± 5°C, the temperature of the fourth section is 255°C ± 5°C, the temperature of the fifth section is 265°C ± 5°C, the temperature of the sixth section is 265°C ± 5°C, the temperature of the seventh section is 275±5°C, the temperature of the eighth section is 275±5°C, the temperature of the ninth section is 265±5°C, and the temperature of the tenth section is 265±5°C. The head temperature is 285°C ± 5°C, the screw speed is 300rpm~400rpm, and the vacuum degree is -0.5MPa~-0.9MPa.

[0073] Comparative Example 3

[0074] 58.5 parts of polycarbonate, 40 parts of silicon copolymer polycarbonate, 0.3 parts of potassium benzenesulfonylbenzenesulfonate flame retardant, 0.3 parts of silicone flame retardant (octaglycidyl cage polysilsesquioxane), 0.3 parts of 4-hydroxy-2,2,6,6-tetramethylpiperidinyl nitroxide free radical, 0.4 parts of anti-dripping agent, 0.1 parts of antioxidant 168, 0.1 parts of antioxidant 1076, and 0.4 parts of pentaerythritol stearate. (1) Mixing: Add the above-mentioned formula components into a high-speed mixer and stir for 5 minutes to obtain a mixed material; (2) Extrusion granulation: Add the mixed material into a twin-screw extruder for granulation. The processing temperature of each section of the twin-screw extruder is as follows: the temperature of the first section is 225°C ± 5°C, the temperature of the second section is 255°C ± 5°C, the temperature of the third section is 255°C ± 5°C, the temperature of the fourth section is 255°C ± 5°C, the temperature of the fifth section is 265°C ± 5°C, the temperature of the sixth section is 265°C ± 5°C, the temperature of the seventh section is 275±5°C, the temperature of the eighth section is 275±5°C, the temperature of the ninth section is 265±5°C, and the temperature of the tenth section is 265±5°C. The head temperature is 285°C ± 5°C, the screw speed is 300rpm~400rpm, and the vacuum degree is -0.5MPa~-0.9MPa.

[0075] Comparative Example 4

[0076] 58.5 parts of polycarbonate, 40 parts of silicon copolymer polycarbonate, 0.1 parts of potassium perfluorobutanesulfonate flame retardant, 0.3 parts of silicone flame retardant (trisilanol phenyl cage polysilsesquioxane), 0.4 parts of anti-dripping agent, 1680.2 parts of antioxidant, 10760.2 parts of antioxidant, and 0.4 parts of pentaerythritol stearate. (1) Mixing: Add the above-mentioned formula components into a high-speed mixer and stir for 5 minutes to obtain a mixed material; (2) Extrusion granulation: Add the mixed material into a twin-screw extruder for granulation. The processing temperature of each section of the twin-screw extruder is as follows: the temperature of the first section is 225°C ± 5°C, the temperature of the second section is 255°C ± 5°C, the temperature of the third section is 255°C ± 5°C, the temperature of the fourth section is 255°C ± 5°C, the temperature of the fifth section is 265°C ± 5°C, the temperature of the sixth section is 265°C ± 5°C, the temperature of the seventh section is 275±5°C, the temperature of the eighth section is 275±5°C, the temperature of the ninth section is 265±5°C, and the temperature of the tenth section is 265±5°C. The head temperature is 285°C ± 5°C, the screw speed is 300rpm~400rpm, and the vacuum degree is -0.5MPa~-0.9MPa.

[0077] Comparative Example 5

[0078] 58.5 parts of polycarbonate, 40 parts of silicon copolymer polycarbonate, 0.1 parts of potassium perfluorobutanesulfonate flame retardant, 0.3 parts of 4-isocyanate-2,2,6,6-tetramethylpiperidin-1-oxyl free radical, 0.4 parts of anti-dripping agent, 1680.2 parts of antioxidant, 10760.2 parts of antioxidant, and 0.4 parts of pentaerythritol stearate. (1) Mixing: Add the above-mentioned formula components into a high-speed mixer and stir for 5 minutes to obtain a mixed material; (2) Extrusion granulation: Add the mixed material into a twin-screw extruder for granulation. The processing temperature of each section of the twin-screw extruder is as follows: the temperature of the first section is 225°C ± 5°C, the temperature of the second section is 255°C ± 5°C, the temperature of the third section is 255°C ± 5°C, the temperature of the fourth section is 255°C ± 5°C, the temperature of the fifth section is 265°C ± 5°C, the temperature of the sixth section is 265°C ± 5°C, the temperature of the seventh section is 275±5°C, the temperature of the eighth section is 275±5°C, the temperature of the ninth section is 265±5°C, and the temperature of the tenth section is 265±5°C. The head temperature is 285°C ± 5°C, the screw speed is 300rpm~400rpm, and the vacuum degree is -0.5MPa~-0.9MPa.

[0079] Comparative Example 6

[0080] 58.5 parts of polycarbonate, 40 parts of silicon copolymer polycarbonate, 0.1 parts of potassium perfluorobutane sulfonate flame retardant, 0.3 parts of silicone flame retardant (trisilol phenyl cage polysilsesquioxane), 0.3 parts of 4-isocyanate-2,2,6,6-tetramethylpiperidin-1-oxyl free radical, 0.4 parts of anti-dripping agent, 0.2 parts of antioxidant 168, 0.2 parts of antioxidant 1076, and 0.4 parts of pentaerythritol stearate. (1) Mixing: Add the above-mentioned formula components into a high-speed mixer and stir for 5 minutes to obtain a mixed material; (2) Extrusion granulation: Add the mixed material into a twin-screw extruder for granulation. The processing temperature of each section of the twin-screw extruder is as follows: the temperature of the first section is 225°C ± 5°C, the temperature of the second section is 255°C ± 5°C, the temperature of the third section is 255°C ± 5°C, the temperature of the fourth section is 255°C ± 5°C, the temperature of the fifth section is 265°C ± 5°C, the temperature of the sixth section is 265°C ± 5°C, the temperature of the seventh section is 275±5°C, the temperature of the eighth section is 275±5°C, the temperature of the ninth section is 265±5°C, and the temperature of the tenth section is 265±5°C. The head temperature is 285°C ± 5°C, the screw speed is 300rpm~400rpm, and the vacuum degree is -0.5MPa~-0.9MPa.

[0081] Comparative Example 7

[0082] Trisilanol phenyl cage polysilsesquioxane is dissolved in tetrahydrofuran in an equivalent ratio of 3:1 between the hydroxyl group and the isocyanate group of 4-isocyanate-2,2,6,6-tetramethylpiperidin-1-oxyl free radical, dibutyltin dilaurate is used as a catalyst, and the reaction is stirred at 20°C for 24 hours. After drying, a POSS grafted nitroxide free radical compound is obtained, which is a composite flame retardant.

[0083] 63.5 parts of polycarbonate, 35 parts of silicon copolymer polycarbonate, 0.1 parts of potassium perfluorobutyl sulfonate flame retardant, 0.3 parts of compound flame retardant, 0.4 parts of anti-dripping agent, 1680.2 parts of antioxidant, 10760.2 parts of antioxidant, and 0.4 parts of pentaerythritol stearate. (1) Mixing: Add the above-mentioned formula components into a high-speed mixer and stir for 5 minutes to obtain a mixed material; (2) Extrusion granulation: Add the mixed material into a twin-screw extruder for granulation. The processing temperature of each section of the twin-screw extruder is as follows: the temperature of the first section is 225°C ± 5°C, the temperature of the second section is 255°C ± 5°C, the temperature of the third section is 255°C ± 5°C, the temperature of the fourth section is 255°C ± 5°C, the temperature of the fifth section is 265°C ± 5°C, the temperature of the sixth section is 265°C ± 5°C, the temperature of the seventh section is 275±5°C, the temperature of the eighth section is 275±5°C, the temperature of the ninth section is 265±5°C, and the temperature of the tenth section is 265±5°C. The head temperature is 285°C ± 5°C, the screw speed is 300rpm~400rpm, and the vacuum degree is -0.5MPa~-0.9MPa.

[0084] Comparative Example 8

[0085] Trisilanol phenyl cage polysilsesquioxane is dissolved in tetrahydrofuran in an equivalent ratio of 3:1 between the hydroxyl group and the isocyanate group of 4-isocyanate-2,2,6,6-tetramethylpiperidin-1-oxyl free radical, dibutyltin dilaurate is used as a catalyst, and the reaction is stirred at 20°C for 24 hours. After drying, a POSS grafted nitroxide free radical compound is obtained, which is a composite flame retardant.

[0086] 73.5 parts of polycarbonate, 25 parts of silicon copolymer polycarbonate, 0.1 parts of potassium perfluorobutyl sulfonate flame retardant, 0.3 parts of compound flame retardant, 0.4 parts of anti-dripping agent, 1680.2 parts of antioxidant, 10760.2 parts of antioxidant, and 0.4 parts of pentaerythritol stearate. (1) Mixing: Add the above-mentioned formula components into a high-speed mixer and stir for 5 minutes to obtain a mixed material; (2) Extrusion granulation: Add the mixed material into a twin-screw extruder for granulation. The processing temperature of each section of the twin-screw extruder is as follows: the temperature of the first section is 225°C ± 5°C, the temperature of the second section is 255°C ± 5°C, the temperature of the third section is 255°C ± 5°C, the temperature of the fourth section is 255°C ± 5°C, the temperature of the fifth section is 265°C ± 5°C, the temperature of the sixth section is 265°C ± 5°C, the temperature of the seventh section is 275±5°C, the temperature of the eighth section is 275±5°C, the temperature of the ninth section is 265±5°C, and the temperature of the tenth section is 265±5°C. The head temperature is 285°C ± 5°C, the screw speed is 300rpm~400rpm, and the vacuum degree is -0.5MPa~-0.9MPa.

[0087] Comparative Example 9

[0088] Trisilanol phenyl cage polysilsesquioxane is dissolved in tetrahydrofuran in an equivalent ratio of 3:1 between the hydroxyl group and the isocyanate group of 4-isocyanate-2,2,6,6-tetramethylpiperidin-1-oxyl free radical, dibutyltin dilaurate is used as a catalyst, and the reaction is stirred at 20°C for 24 hours. After drying, a POSS grafted nitroxide free radical compound is obtained, which is a composite flame retardant.

[0089] 58.5 parts of polycarbonate, 40 parts of silicon copolymer polycarbonate, 0.1 parts of potassium perfluorobutyl sulfonate flame retardant, 0.3 parts of ultraviolet absorber UV-234, 0.4 parts of anti-dripping agent, 1680.2 parts of antioxidant, 10760.2 parts of antioxidant, and 0.4 parts of pentaerythritol stearate. (1) Mixing: Add the above-mentioned formula components into a high-speed mixer and stir for 5 minutes to obtain a mixed material; (2) Extrusion granulation: Add the mixed material into a twin-screw extruder for granulation. The processing temperature of each section of the twin-screw extruder is as follows: the temperature of the first section is 225°C ± 5°C, the temperature of the second section is 255°C ± 5°C, the temperature of the third section is 255°C ± 5°C, the temperature of the fourth section is 255°C ± 5°C, the temperature of the fifth section is 265°C ± 5°C, the temperature of the sixth section is 265°C ± 5°C, the temperature of the seventh section is 275±5°C, the temperature of the eighth section is 275±5°C, the temperature of the ninth section is 265±5°C, and the temperature of the tenth section is 265±5°C. The head temperature is 285°C ± 5°C, the screw speed is 300rpm~400rpm, and the vacuum degree is -0.5MPa~-0.9MPa.

[0090] Performance tests were performed on Examples 1 to 7 and Comparative Examples 1 to 9, and the results are shown in Tables 1 and 2:

[0091] Table 1

[0092]

[0093] Table 2

[0094]

[0095]

[0096] The difference between Example 1, Example 2 and Example 3, and Example 4, Example 5 and Example 6 is that the amount of compound flame retardant is different. By comparison, it can be seen that increasing the amount of compound flame retardant can significantly improve the flame retardant properties of the material. Compared with Example 2 and Example 6, potassium benzenesulfonylbenzenesulfonate and potassium perfluorobutylsulfonate and compound flame retardant are added in Example 7. In Example 2, the content of potassium benzenesulfonylbenzenesulfonate is reduced while the content of potassium perfluorobutylsulfonate is increased, and in Example 6, the content of compound flame retardant is reduced while the content of potassium benzenesulfonylbenzenesulfonate is increased. The flame retardant effect can reach 0.5mmV-0 (Example 7), indicating that there is a good compounding effect between sulfonate flame retardant and compound flame retardant.

[0097] Example 3, Comparative Example 1, Comparative Example 2 and Comparative Example 3 are potassium benzenesulfonylbenzenesulfonate systems, the difference being that Example 3 is a compound flame retardant, Comparative Example 1 is an organosilicon flame retardant, Comparative Example 2 is a nitroxide free radical, and Comparative Example 3 is an organosilicon flame retardant and a nitroxide free radical. Example 6, Comparative Example 4, Comparative Example 5 and Comparative Example 6 are potassium perfluorobutyl sulfonate systems, the difference being that Example 6 is a compound flame retardant, Comparative Example 4 is an organosilicon flame retardant, Comparative Example 5 is a nitroxide free radical, and Comparative Example 6 is an organosilicon flame retardant and a nitroxide free radical. By comparison, it can be seen that the addition of organosilicon flame retardants and nitroxide free radicals alone can only exert their respective limited characteristics and do not have efficient flame retardant properties. Among them, the retention rates of xenon lamp aging tensile strength and notched impact strength of Comparative Examples 1 and 4 are poor, because there is no weather-resistant component in the system, i.e., there is no nitroxide free radical. The tensile strength retention rate and notched impact strength retention rate of Example 3 are similar to those of Comparative Examples 2 and 3, and the tensile strength retention rate of Example 6 is similar to that of Comparative Examples 5 and 6. This is because the nitroxide free radicals in its components play the same weathering properties as the hindered amine light stabilizer, that is, the stable nitroxide free radicals can effectively capture the active free radicals generated by the photo-oxidative degradation of the polymer, effectively preventing the chain reaction of degradation. Moreover, the flame retardancy of Example 3 can reach 0.8mmV-0, and the flame retardancy of Example 6 can reach 0.5mmV-0, which is not only the flame retardant effect of the sulfonate flame retardant, but also the synergistic flame retardant effect of the organosilicon flame retardant (i.e., compound flame retardant) with nitroxide free radicals in the structure. This is because at high temperatures, the organosilicon flame retardant will form a dense silicon oxide film layer similar to a ceramic structure, which effectively prevents molten droplets from falling; and the organosilicon flame retardant will catalyze the polymer to form a dense carbon layer, effectively isolating oxygen and heat. In addition, the structure of the nitroxide free radical will simultaneously play the characteristic of capturing the active free radicals released by combustion in situ, and effectively quench the active free radicals synchronously, further improving the flame retardant efficiency. The organosilicon flame retardant and nitroxide free radicals in Comparative Examples 3 and 6 are evenly dispersed, and cannot play the synergistic flame retardant characteristics in situ, and their flame retardant performance is poor. The difference between Example 6 and Comparative Examples 7 and 8 is that the ratio of polycarbonate and silicon copolymer polycarbonate is different. By comparison, it can be seen that increasing the ratio of silicon copolymer polycarbonate can significantly improve the low-temperature impact strength and thin-wall flame retardant performance, that is, the ratio of polycarbonate and silicon copolymer polycarbonate in this application is preferably less than 1.5. The difference between Example 6 and Comparative Example 9 is that the compound flame retardant is replaced with an ultraviolet absorber. By comparison, it can be seen that the compound flame retardant has the same weathering level as the ultraviolet absorber, and the tensile strength retention rate and impact strength retention rate are similar. This is because the stably existing nitroxide free radicals can effectively capture the active free radicals generated by the photo-oxidative degradation of the polymer, effectively prevent the degradation of the polymer, and improve the mechanical property retention rate of the polymer.

[0098] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0099] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A polycarbonate material, characterized in that: The raw materials include 40 to 80 parts of polycarbonate, 20 to 60 parts of silicon copolymer polycarbonate, 0.1 to 0.5 parts of sulfonate flame retardant, 0.1 to 0.5 parts of compound flame retardant, 0.3 to 0.8 parts of anti-dripping agent, 0.1 to 0.4 parts of antioxidant and 0.2 to 0.8 parts of lubricant in parts by weight. The compound flame retardant is an organic silicon flame retardant with nitroxide free radical in its structure, and the compound flame retardant is obtained by group reaction between an organic silicon flame retardant containing active groups and a nitroxide free radical compound containing active groups.

2. A polycarbonate material according to claim 1, characterized in that: The mass ratio of polycarbonate to silicon copolymer polycarbonate is less than 1.

5.

3. A polycarbonate material according to claim 1, characterized in that: The polycarbonate is bisphenol A polycarbonate, and the melt mass flow rate is 3 to 20 g / 10 min; And / or, the silicon copolymer polycarbonate melt has a mass flow rate of 3 to 10 g / 10 min.

4. A polycarbonate material according to claim 1, characterized in that: The sulfonate flame retardant includes at least one of potassium benzenesulfonylbenzenesulfonate, potassium perfluorobutylsulfonate and sodium 2,4,5-trichlorobenzenesulfonate.

5. A polycarbonate material according to claim 1, characterized in that: The organic silicon flame retardant is a cage-type polysilsesquioxane, and the general formula of the cage-type polysilsesquioxane is (RSiO3 / 2)n, wherein n is an even number ≥6, and R is an organic group connected to the Si atom.

6. A polycarbonate material according to claim 5, characterized in that: The organic group in the structure of the organosilicon flame retardant is an active group, and the number of the active group is at least one.

7. A polycarbonate material according to claim 6, characterized in that: The active group in the structure of the organosilicon flame retardant is selected from one of epoxy, carboxyl, hydroxyl, amino, isocyanate, vinyl, allyl and thiocyanate.

8. The polycarbonate material according to claim 1, characterized in that: The organosilicon flame retardant is any one of octaepoxy cage-type polysilsesquioxane, octavinyl cage-type polysilsesquioxane, octaglycidyl cage-type polysilsesquioxane, octacarboxyl cage-type polysilsesquioxane, acrylate cage-type polysilsesquioxane, allyl isobutyl cage-type polysilsesquioxane, trinorbornene isobutyl cage-type polysilsesquioxane, epoxy cyclohexyl cage-type polysilsesquioxane, trisilanol phenyl cage-type polysilsesquioxane, and octaammonium cage-type polysilsesquioxane.

9. The polycarbonate material according to claim 1, characterized in that: The nitroxide free radical compound has at least one nitroxide free radical in its structure.

10. The polycarbonate material according to claim 1, characterized in that: The nitroxide free radical compound has at least one active group in its structure.

11. A polycarbonate material according to claim 10, characterized in that: The active group in the structure of the nitroxide free radical compound is selected from one of epoxy, carboxyl, hydroxyl, amino, isocyanate, vinyl, allyl and thiocyanate.

12. The polycarbonate material according to claim 1, characterized in that: The nitroxide free radical compound is 2,2,6,6-tetramethylpiperidine-1-oxyl-4-amino-4-carboxylic acid, 4-(2-bromoacetamide)-2,2,6,6-tetramethylpiperidine-1-oxyl free radical, 4-epoxypropyloxy-2,2,6,6-tetramethylpiperidine-1-oxyl free radical, 4-amino-2,2,6,6-tetramethylpiperidine-1-oxyl free radical, 4-hydroxy-2,2,6,6-tetramethylpiperidine nitroxide free radical, 4-carboxyl-2,2,6,6-tetramethylpiperidine-1-oxyl free radical, 4-isopropyloxy-2,2,6,6-tetramethylpiperidine-1-oxyl free radical, One of cyanate-2,2,6,6-tetramethylpiperidine-1-oxyl free radical, 4-isothiocyanato-2,2,6,6-tetramethylpiperidine-1-oxyl free radical, 4-methacryloyloxy-2,2,6,6-tetramethylpiperidine-1-oxyl free radical, 4-(4-chloroformyl-benzoate)-2,2,6,6-tetramethylpiperidine-1-oxyl free radical, 3-carbamoyl-2,2,5,5-tetramethyltetrahydropyrrole nitrogen oxide free radical, and 3-carboxy-2,2,5,5-tetramethylpyrrolidine-1-oxyl free radical.

13. The polycarbonate material according to claim 1, characterized in that: The preparation process of compound flame retardant is as follows: A catalyst is added to a solvent of an organosilicon flame retardant containing an active group and a nitroxide free radical compound containing an active group, the reaction temperature is 20 to 60° C., the reaction is stirred for 6 to 24 hours, and then the mixture is extracted and dried.

14. The polycarbonate material according to claim 1, characterized in that: The anti-drip agent is a polytetrafluoroethylene anti-drip agent coated with acrylonitrile-styrene copolymer; and / or, the antioxidant comprises at least two of antioxidant 1076, antioxidant 1010, antioxidant 168, and antioxidant 627A; And / or, the lubricant is at least one of pentaerythritol stearate, silicone powder and polyester wax.

15. A method for preparing a polycarbonate material according to any one of claims 1 to 14, characterized in that the steps include: (1) Mixing: Mixing the formulated amounts of polycarbonate, silicon copolymer polycarbonate, sulfonate flame retardant, compound flame retardant, anti-dripping agent, antioxidant and lubricant to obtain a mixed material; (2) Extrusion granulation: adding the mixed material to a twin-screw extruder for granulation to obtain a high-toughness, thin-wall, halogen-free, flame-retardant polycarbonate material.

16. The method for preparing a polycarbonate material according to claim 15, characterized in that: The processing temperatures of each zone of the twin-screw extruder are as follows: zone one temperature is 225°C±5°C, zone two temperature is 255°C±5°C, zone three temperature is 255°C±5°C, zone four temperature is 255°C±5°C, zone five temperature is 265°C±5°C, zone six temperature is 265°C±5°C, zone seven temperature is 275±5°C, zone eight temperature is 275±5°C, zone nine temperature is 265±5°C, zone ten temperature is 265±5°C; the die head temperature is 285°C±5°C, the screw speed is 300rpm~400rpm, and the vacuum degree is -0.5MPa~-0.9MPa.

17. Use of a polycarbonate material according to any one of claims 1 to 14, characterized in that: Used to prepare high-toughness thin-walled halogen-free flame-retardant polycarbonate material parts.

18. The use of a polycarbonate material according to claim 17, characterized in that: The thickness of the high-toughness thin-wall halogen-free flame-retardant polycarbonate material parts is 0.5 to 0.8 mm.

Citation Information

Patent Citations

  • Halogen-free flame-retardant PC (polycarbonate) and preparation method thereof

    CN106349676A

  • Polycarbonate composition and preparation method thereof

    CN101519529A

  • Aryl POSS flame retardant with free radical quenching function and synthetic method and application thereof

    CN106349479A

  • Glass-fiber-reinforced flame-retardant polycarbonate composite material, and preparation method and applications thereof

    CN110157174A

  • Single-component intumescent flame retardant with free radical quenching function, preparation method and applications thereof

    CN110776635A

Cited By

  • Polycarbonate / styrene composite material as well as preparation method and application thereof

    CN120484477A

  • A polycarbonate / styrene composite material, its preparation method and application

    CN120484477B

  • Flexible insulating sling for high-voltage operation and preparation method thereof

    CN121394080A